Evidence for charge-based mimicry in anti dsDNA antibody generation. Issue 132 (October 2022) - Bruschi, Maurizio; Angeletti, Andrea; Kajana, Xhuliana; Moroni, Gabriella; Sinico, Renato Alberto; Fredi, Micaela; Vaglio, Augusto; Cavagna, Lorenzo; Pratesi, Federico; Migliorini, Paola; Locatelli, Francesco; Pazzola, Giulia; et al.
Abstract: Mechanisms for the generation of anti-dsDNA autoantibodies are still not completely elucidated. One theory states that dsDNA interacts for mimicry with antibodies raised versus other antigens but molecular features for mimicry are unknown. Here we show that, at physiological acid-base balance, anti-Annexin A1 binds IgG2 dsDNA in a competitive and dose-dependent way with Annexin A1 and that the competition between the two molecules is null at pH 9. On the other hand, these findings also show that dsDNA and Annexin A1 interact with their respective antibodies on a strictly pH-dependent basis: in both cases, the binding was minimal at pH 4 and maximal at pH9-10. The anionic charge of dsDNA is mainly conferred by the numerous phosphatidic residues. The epitope binding site of Annexin A1 for anti-Annexin A1 IgG2 was here characterized as a string of 34 amino acids at the NH2 terminus, 10 of which are anionic. Circulating levels of anti-dsDNA and anti-Annexin A1 IgG2 antibodies were strongly correlated in patients with systemic lupus erythematosus (n 496) and lupus nephritis (n 425) stratified for age, sex, etc. These results show that dsDNA competes with Annexin A1 for the binding with anti-Annexin A1 IgG2 on a dose and charged mediated base, being able to display an inhibition up to 75%. This study provides the first demonstration that dsDNA may interact with antibodies raised versus other anionic molecules (anti-Annexin A1 IgG2) because of charge mimicry and this interaction may contribute to anti-dsDNA antibodies generation. Highlights: dsDNA may interact for mimicry with antibodies raised versus other antigens. AnnexinA1 is here described as the first mimicker of dsDNA acting on a charge basis. . Many PO4 residues of dsDNA justifies the pH dependent interaction with specific IgG2. . The binding epitope of AnnexinA1 was characterized as an anionic peptide at the NH2. . These findings demonstrate a new molecular mechanism for anti-dsDNA generation.